Isto não é um artigo sobre pornografia de vingança: a punibilidade da divulgação não consentida de imagens íntimas (De Legibus - Law Journal, 2022)
Everyday many thousands of women, all over the world, watch helplessly to the disclosure of their intimate content, especially of a sexual nature. With this study, we propose to analyze the kaleidoscope of this intimate publicity, seeking to investigate how it is processed, the agent's motivations, emphasize the damage produced, analyze the legal consequences of these facts and, if these are unsatisfactory, launch into the debate suggestions for the legal system to respond effectively to the topics raised.The research methodology used is based on the combination of three theoretical-methodological axes, embodying (i) dogmatic research, with regard to recourse to contemporary doctrine, jurisprudence and legislation, (ii) socio-legal research, seeking to identify and analyze the inconsistencies of the legal system relating it to other sciences such as sociology and psychology, inter alia, and (iii) in epistemological research, based on the study of the legal system as a whole and the legal norms and jusphilosophical concepts.
Keywords: Right to privacy; Unauthorized disclosure of intimate content; gender violence.